A Double-Blind Randomized Comparison of Continuous Interscalene, Supraclavicular, and Suprascapular Blocks for Total Shoulder Arthroplasty. Issue 3 (1st May 2017) - Auyong, David B.; Yuan, Stanley C.; Choi, Daniel S.; Pahang, Joshuel A.; Slee, April E.; Hanson, Neil A.
Abstract : Background and Objectives: Continuous brachial plexus blocks at the interscalene level are associated with known diaphragm dysfunction from phrenic nerve paresis. More distal blocks along the brachial plexus may provide postsurgical analgesia while potentially having less effect on diaphragm function. Continuous interscalene, continuous supraclavicular, and continuous suprascapular nerve blocks were evaluated for respiratory function and analgesia after total shoulder arthroplasty. Methods: After ethics board approval, subjects presenting for total shoulder arthroplasty were planned for randomization in a 1:1:1 ratio of a continuous interscalene, supraclavicular, or suprascapular block. The primary outcome was the assessment of vital capacity after 24 hours of continuous nerve block infusion (6 mL/h; 0.2% ropivacaine), without an initial bolus of local anesthetic during catheter placement. Additional outcomes included diaphragm excursion, pain scores, opioid consumption, and adverse effects. Results: Seventy-five subjects, 25 per group, completed the study. At 24 hours of continuous infusion only (no initial block bolus), the mean vital capacity reduction in the continuous interscalene control group was 991 mL (95% confidence interval [CI], 820–1162). Compared to the interscalene group, the continuous supraclavicular group had a mean vital capacity reduction of 803 mL (95% CI, 616–991; P = 0.322). The continuous suprascapular group had a significantly improved mean vital capacity reduction of 464 mL (95% CI, 289–639; P < 0.001) when similarly compared against the interscalene group. A relative compromise in ultrasound-measured diaphragm excursion was identified in the interscalene group compared to both the supraclavicular group ( P = 0.012) and the suprascapular group ( P < 0.001). Mean pain scores on an 11-point scale (2.2, 1.6, and 2.6) and 24-hour opioid consumption (13.8 mg, 9.9 mg, and 21.8 mg) for groups interscalene, supraclavicular, and suprascapular, respectively, did not show statistically significant differences. Less adverse effects (Horner syndrome, dyspnea, and hoarseness) were noted in the suprascapular group when compared with the interscalene group ( P = 0.002). Conclusions: A continuous suprascapular block may be a useful analgesic alternative to the interscalene or supraclavicular approaches when the preservation of lung function is a priority after shoulder replacement surgery.